ASSESSING THE ACQUISITION OF INFORMATION QUESTIONS IN ENGLISH MADE BY THE ELEVENTH GRADE STUDENTS OF SMK SARASWATI DENPASAR IN ACADEMIC YEAR 2009/2010 - Kumara, Dewa Gede Agung Gana (Fakultas Keguruan dan Ilmu Pendidikan (FKIP) Universitas Mahasaraswati Denpasar, 2011)
This study was undertaken in order to assess the acquisition of information questions by the eleventh grade students of SMK Saraswati Denpasar in academic year 2009/2010. The undertaking of the study was motivated by the fact that information questions are the fundamental basis of good communication skills in English. This study was intended to answer the research question: To what extent is the acquisition of the eleventh grade students of SMK Saraswati Denpasar in constructing information question in English. This study made use of an ex-post facto research design. The population of the study was the eleventh grade students of accountancy department which consists of two classes with the total students of 79 altogether. They were considered to have homogeneous characteristic. In this study, only 40 students were determined as the objects by using quota random sampling technique with lottery system. The data obtained in the study which were in the form of raw scores showing the subjects’ acquisition of information questions of the eleventh grade students of SMK Saraswati Denpasar, were analyzed with norm reference measure with five standard values. It clearly showed that: (1) there are 5 subjects (12.5%) out of 40 subjects under study who got excellent ability in asking information questions in English, (2) there are 11 subjects (27.5%) out of 40 subjects under study who got good ability in asking information questions in English. (3) there are 13 subjects (32.5%) out of 40 subjects under study who got sufficient ability in asking information questions in English and (4) there are 11 subjects (27.5%) out of 40 subjects under study who got insufficient ability in asking information questions in English. In general these research findings revealed that the acquisition of information questions by the eleventh grade students of SMK Saraswati Denpasar is remarked as good, where the number of subjects who got insufficient acquisition in information questions were under 50% or half of the number of subjects understudy. The number of students who got insufficient acquisition in information questions is only 11 subjects or 27.5% out of 40 subjects understudy. The findings of the study have limited validity and reliability, because it made use of an ex-post facto research design. Therefore, the research findings should be carefully depended upon.